2020
DOI: 10.18203/2349-3291.ijcp20200120
|View full text |Cite
|
Sign up to set email alerts
|

Serum immunoglobulin E and absolute eosinophil count as markers of severity in childhood asthma

Abstract: Background: Asthma is a chronic inflammatory condition of the airways resulting in increased airway reactivity to a variety of stimuli like allergens, irritants, viruses and exercise. There is a strong association between the exposure of allergens and development of asthmatic symptoms. A hypersensitivity reaction initiated by immunologic mechanisms mediated by Immunoglobulin E (IgE) antibodies occurs in allergic asthma. IgE and eosinophils play an important role in the inflammatory process resulting in bronchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
3
1
Order By: Relevance
“…The study showed no significant association between total serum IgE levels and asthma severity (P = 0.955). The results were inconsistent with other previous results [21][22][23] , which mentioned that the total serum IgE levels increased as the severity of asthma increased. The difference in the current results compared with the previous results, was due to the effect of high-dose inhaled corticosteroids (ICS) combined with a long-acting â2 agonist (LABA) on total serum IgE levels in severe asthma.…”
Section: Correlation Between Total Ige and Il-4 Levels In Asthmatic P...contrasting
confidence: 99%
“…The study showed no significant association between total serum IgE levels and asthma severity (P = 0.955). The results were inconsistent with other previous results [21][22][23] , which mentioned that the total serum IgE levels increased as the severity of asthma increased. The difference in the current results compared with the previous results, was due to the effect of high-dose inhaled corticosteroids (ICS) combined with a long-acting â2 agonist (LABA) on total serum IgE levels in severe asthma.…”
Section: Correlation Between Total Ige and Il-4 Levels In Asthmatic P...contrasting
confidence: 99%
“…In eosinophil value in blood, it is an indirect marker of airway inflammation in asthma. In addition, the absolute eosinophil count in peripheral blood is a widely used laboratory value to indicate the allergic etiology of the disease [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, asthma affected an estimated 262 million people and caused 455,000 deaths ( 2 ). As a result of its escalating global prevalence, asthma poses a daunting challenge to public health infrastructures ( 3 , 4 ). Epidemiological evidence suggests that asthma is a primary culprit of mortality worldwide and a major economic encumbrance on healthcare systems ( 5 ).…”
Section: Introductionmentioning
confidence: 99%